Konsep perempuan shalihah pada lirik â€œAisyah Istri Rasulullahâ€ (Studi ketidakadilan analisis wacana Teun A. Van Dijk) - Nur Kumala (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2020)
The presentation of the lyrics in a song is a form of communication that requires meaning, through the massive lyrics of a song composed entitled